Model answers in pure mathematics for A-level students - Pratt, Gerald Alfred; Schofield, C. W. (Commonwealth and international library. Commonwealth library of model answers., 1966)
Model Answers in Pure Mathematics for A-Level Students provides a set of solutions that indicate what is required and expected in an Advanced Level examination in Pure Mathematics.